A quasi-solid-state photothermal supercapacitor via enhanced solar energy harvest. Issue 4 (3rd January 2020) - Zhao, Mingyu; Li, Yaling; Lin, Feng; Xu, Yunshi; Chen, Leilei; Jiang, Weicun; Jiang, Ting; Yang, Shuguang; Wang, Yi
Abstract : A mesoporous carbon nanosphere-intercalated graphene hydrogel with a hierarchical porous architecture is prepared as a flexible quasi-solid-state photothermal supercapacitor via solar irradiation. Abstract : The development of flexible supercapacitors with high volumetric capacitance and energy density for outdoor wearable electronics, especially for applications in low-temperature environments, remains an urgent challenge. Here, compressible film electrodes architected by an N-doped mesoporous carbon nanosphere-intercalated 3D graphene hydrogel (N-MCN@GH) composite were developed for energy storage applications. This N-MCN@GH electrode exhibited a hierarchical porous network with a large accessible surface area for rapid electron transportation and massive ion migration via uniform N-MCN bracing in conductive graphene; therefore, it could serve as a flexible supercapacitor and deliver a total volumetric ( vs. the whole device) capacitance of 8.1 F cm −3 with a stable energy density of 1.12 mW h cm −3 at a power density of 13.30 mW cm −3 . Very interestingly, this flexible N-MCN@GH electrode showed enhanced solar absorption and could achieve efficient solar-thermal conversion for the prevention of capacitance decay under low temperature environmental conditions. Additionally, the packaging of the photothermal supercapacitor in a transparent PET membrane preserved its enhanced photothermal capacitance performance. This work provides an innovative strategy to obtain flexible supercapacitors for practical applications and also initiates a new concept for optical/temperature sensing devices.